2019
DOI: 10.1101/582353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local cortical desynchronization and pupil-linked arousal differentially shape brain states for optimal sensory performance

Abstract: Instantaneous brain states have consequences for our sensation, perception, and behaviour. Fluctuations in arousal and neural desynchronization likely pose perceptually relevant states. However, their relationship and their relative impact on perception is unclear. We here show that, at the single-trial level in humans, local desynchronization in sensory cortex (expressed as time-series entropy) versus pupil-linked arousal differentially impact perceptual processing. While we recorded electroencephalography (E… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 81 publications
13
50
0
Order By: Relevance
“…This result supports the model that phasic neuromodulatory signals that occur naturally are strongest during intermediate levels of tonic neuromodulatory activity (Aston-Jones and Cohen, 2005). This model is further supported by recent observations that tonic arousal predicts nonmonotonic (inverted U) changes in the signal-to-noise ratio of sensory cortical responses and perceptual sensitivity (McGinley et al, 2015a;Schriver et al, 2018;Waschke et al, 2019). Note that we observed the inverted U relationship after correcting for a general reversion to mean.…”
Section: Discussionsupporting
confidence: 90%
“…This result supports the model that phasic neuromodulatory signals that occur naturally are strongest during intermediate levels of tonic neuromodulatory activity (Aston-Jones and Cohen, 2005). This model is further supported by recent observations that tonic arousal predicts nonmonotonic (inverted U) changes in the signal-to-noise ratio of sensory cortical responses and perceptual sensitivity (McGinley et al, 2015a;Schriver et al, 2018;Waschke et al, 2019). Note that we observed the inverted U relationship after correcting for a general reversion to mean.…”
Section: Discussionsupporting
confidence: 90%
“…Future studies could also explore how neural variability quenching and boosting in different timescales are related to various aspects of decision making such as perceptual sensitivity and different kinds of biases ( Fleming et al, 2010 ; Talluri et al, 2018 ; Urai et al, 2019 ), as well as to confidence and metacognitive processes ( Fleming and Dolan, 2012 ; Yeung and Summerfield, 2012 ). Furthermore, individual decision bias has also been linked to the magnitude of transient dilations of the pupil ( de Gee et al, 2017 , de Gee et al, 2014 ) and to entropy of EEG ( Waschke et al, 2019 ), suggesting that pupil-linked neuromodulation ( Joshi and Gold, 2020 ) could be related to decision bias through adjustments to moment-to-moment neural variability. Further investigation of such relationships could yield fruitful insights about the neurochemical mechanisms underlying associations between neural variability and higher order cognitive function ( Alavash et al, 2018 ; Garrett et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha oscillations are abundant during detachment from the sensory environment in wakefulness and considered an index of low arousal (Torsvall and Akerstedt, 1987b;Drapeau and Carrier, 2004b). Alpha oscillations are believed to represent an "idling" state of cortical activity (Steriade, 2001;Palva and Palva, 2007) that is expected to be anti-correlated with arousal-promoting activity, such as that of the LC-NE system, and bias sensory perception (Waschke et al, 2019). A recent study that used long 2min tVNS on the neck also found that tVNS attenuates alpha and theta oscillation (Lewine et al, 2019).…”
Section: Vnsmentioning
confidence: 99%